(untitled) (Medical Forum Monthly, 2021)
Objective: To determine level of anxiety in pregnant females during covid-19 using CAS scale and to determine pregnant women’s maternal and fetal health concerns during COVID-19. Study Design: Descriptive Cross sectional study Place and Duration of Study: This study was conducted at the Outpatient department of Obstetrics and Gynaecology Isra University Hospital Hyderabad from January 2021 to March 2021 for a period of 03 months. Materials and Methods: A convenience sampling technique was used to collect data from 180 pregnant women who had no previous psychiatric, missed abortion, or ectopic pregnancy history. A standardized CAS scale was used to assess each participant's level of anxiety about COVID-19, followed by a self-structured questionnaire to assess women's concerns about foetal and maternal health in the context of COVID-19. Frequency was calculated for all variables. Results: The bulk of our patients were over 35 years old and multigravida, according to our results. Corona related anxiety was found in 63.8% of patients, and it had an impact (58%) on their lives, both in terms of their health (41.3%) and the health of their unborn child (53.8%). Conclusion: Anxiety was shown to be present in majority of pregnant females with most of them being worried about the health of their unborn child.